Grace Roh: capstone - Roh, Grace, artist (Colorado State University. Libraries, 2013)
The artist's statement: My desire for art making has everything to do with my need to make a mark, an imprint, or an impression. I find my peace within the physical act of art making and through the process in which an object is created. The process of meditation through repetition is one of the ways that I have learned to come to terms with the rest of the world. My practice is selfish. I am constantly creating artifacts of myself, whether they are tangible or purely metaphysical. These artifacts serve as a portal to connect myself with the rest of the world, and are used in my performances of ritual and ceremony.
Colorado State University Art Department capstone project.
Capstone contains the artist's statement, a list of works, and images of works.